A review of the current status of the Polydora-complex (Polychaeta: Spionidae) in Australia and a checklist of recorded species - Walker, Lexie M (Zootaxa, 2011)
In 1885 Australia’s first recorded marine pest, a mudworm of the Polydora-complex (Spionidae), was identified on Hunter River, New South Wales, oysters (Saccostrea glomerata Gould, 1850). Mudworm is still a serious pest of cultured molluscs in Australia but, although of great concern to many, relatively little progress has been made in resolving the problem. One hundred and thirty years later the identity and life history of this pest remains unclear. The longevity of this problem in Australia is largely due to unaddressed issues of basic taxonomy. This review addresses these issues by presenting the information currently available on the Polydora-complex species in Australia, including taxonomy; history of discovery in the natural environment and in commercial aquaculture facilities; and ecological information. An updated checklist of Polydora-complex species from Australia is also included. It is hoped that by being explicit about the knowledge gaps and problems they can be addressed, ultimately providing a solid taxonomic background for further research into the Polydora-complex species and resolution of the mudworm problem in Australia.